Líquenes como indicadores de contaminación en el complejo industrial de Betania y la termoeléctrica de Zipaquirá, Cundinamarca - Luis Juan Rubiano (Acta Biológica Colombiana, 1988)
This work evaluates the potential use of lichens as indicators of the quantity and effect of atmospheric polluntants in the zones of influence of the industrial complex of Betania and the thermoelectric plant of Zipaquira in the Department of Cundinamarca, Colombia.